The Comparison of Teaching Strategies Between Male and Female English Teachers in Junior High Schools in Singaraja - Nyoman Audyta Candra Dewi; Putu Artini; Eka Agustini (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the comparison of teaching strategies between male and female English teachers in Junior High School in Bali in implementing the Merdeka Curriculum. This study involved one male teacher and one female teacher. This research used descriptive qualitative research. The findings of this study revealed clear differences in teaching strategies between male and female English teachers at SMP Negeri 2 Sawan. Although the male teacher claimed to apply various modern teaching strategies, classroom observations showed that he relied heavily on lectures and one-way communication. His teaching was directive and used an imperative speaking style, which limited student interaction. In contrast, the female teacher used metacognitive and problem-based learning strategies, which were in line with her attention to student needs and readiness in class. She demonstrated two-way communication and encouraged critical thinking through questions and discussions. In addition, her approach combined social and affective strategies, reflecting a more nurturing and responsive teaching style. These findings suggest that the male teacher's teaching was more authoritative, while the female teacher's teaching was more interactive and student-oriented.